The Students’ Interest Towards the Implementation of Tittle, Examine, look, look, and Setting (TELLS) Strategy - Saparuddin Rosi; Haryanto Atmowardoyo; Fatimah Hidayahni Amin (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
The research investigates the students ‘interest to Using TELLS strategy in learning reading comprehension the eighth-grade students of SMP 23 Makassar. There was one variable used in this research (students’ interest during learning reading comprehension). The aim of this research to determine whether the eighth-grade students of SMP 23 Makassar are interested in using the TELLS strategy for teaching reading comprehension. The research was descriptive quantitative and used questionnaire as instrument for collecting data. The study population consisted of ninth-grade students from SMP 23 Makassar which the subject of the research was VIII 4 class. The researcher utilized cluster random sampling technique with the total consist of 32 students. The result of this research the students were interested in learning using TELLS Strategy in Narrative Text. It is proved by the mean score of students' Interest is 75.04 which is categorized as Interested according to the range of students’ interest score. There are 6 (19 %) of 32 students